2011
DOI: 10.1161/circulationaha.111.025452
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Is Independently Associated With Short-Term Outcomes for Elderly Patients With Non–ST-Segment Elevation Myocardial Infarction

Abstract: Background-For the large and growing population of elderly patients with cardiovascular disease, it is important to identify clinically relevant measures of biological age and their contribution to risk. Frailty is an emerging concept in medicine denoting increased vulnerability and decreased physiological reserves. We analyzed the manner in which the variable frailty predicts short-term outcomes for elderly non-ST-segment elevation myocardial infarction patients. Methods and Results-Patients aged Ն75 years, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
209
2
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(233 citation statements)
references
References 29 publications
10
209
2
12
Order By: Relevance
“…In addition to greater cardiac and noncardiac comorbidities, frail patients had greater deficits in cognition, mobility, and continence. Our findings demonstrating that frailty is not only associated with increased in‐hospital but also midterm all‐cause mortality and hospitalizations following MI are consistent with prior analyses 3, 4, 5, 6. Despite this higher risk, frail patients were managed less aggressively compared with their nonfrail counterparts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to greater cardiac and noncardiac comorbidities, frail patients had greater deficits in cognition, mobility, and continence. Our findings demonstrating that frailty is not only associated with increased in‐hospital but also midterm all‐cause mortality and hospitalizations following MI are consistent with prior analyses 3, 4, 5, 6. Despite this higher risk, frail patients were managed less aggressively compared with their nonfrail counterparts.…”
Section: Discussionsupporting
confidence: 88%
“…However, in patients with significant cardiovascular disease, the prevalence may be as high as 60% 2. Frailty has been associated with increased major adverse cardiac events after myocardial infarction (MI) 3, 4, 5, 6. Mechanisms proposed for worse outcomes are likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus paradoxical that those overweight and obese in midlife life may turn thin and frail in later years. Our findings further suggest that the reported coexistence of CVD and frailty 12,13 is at least partly explained by shared risk factors, and not only secondary effects of disease. These long-term results are in accordance with cross-sectional and old age studies on associations between obesity, smoking and frailty, 23,24 as well as with the Cardiovascular Health Study, 11 which showed that subclinical CVD was associated with frailty.…”
Section: Discussionsupporting
confidence: 68%
“…3,5 In cross-sectional settings, or prospectively in later life, frailty has been associated with both clinical and subclinical cardiovascular disease (CVD). [11][12][13] Accelerated cardiovascular ageing 14 could be one explanation for the proposed relationship between frailty and CVD and also shared biological alterations, such as lowgrade inflammation, 15 may have a role. We have speculated earlier that development of frailty and weight loss therefore could also explain the 'obesity paradox' 16 -better prognosis among older people with overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…48 When examined in the context of coronary artery disease, acute coronary syndromes and percutaneous coronary intervention, frailty has been extensively demonstrated to be a prognostic indicator of adverse cardiac events, rehospitalization and all-cause mortality. [48][49][50][51][52][53] Frailty itself in the elderly HF population is an independent predictor of emergency department visits, hospitalizations and mortality. 54,55 There is a close link between frailty and comorbidities, polypharmacy and malnutrition.…”
Section: Palliative Carementioning
confidence: 99%